Molecular typing of multidrug resistant bacteria isolated from health care professionals’ mobile phone: A pilot study in Jashore, Bangladesh - Hasan, Md Shazid; Chowdhury, Susmita Roy; Meghla, Nigar Sultana; Sakib, Najmuj; Shah, SM Tanjil; Islam, Md Tanvir; Islam, Ovinu Kibria (Bangladesh Journal of Medical Science, 2023)
Background: Nowadays, Health Care Professionals’ (HCPs) are increasingly using mobile phones which may act as reservoirs and vector for transmission of pathogens. The presence of multidrug resistant nosocomial microbes on the surface of mobile phones used by HCPs in hospitals can pose a great public health threat. So, this research was conducted to identify the concerned multi-drug resistant (MDR) bacteria and also to explore the recent status of bacterial contamination on mobile phones of HCPs in the Jashore region of Bangladesh and determine their antibiotic resistance pattern. Methods: Swab samples of mobile phones were collected between June and September 2019 from 24 different users (i.e., manager, worker, doctor and nurse) associated to four distinct hospitals of Jashore region, Bangladesh. After suitable morphological and biochemical identification, we determined their antimicrobial susceptibility by Kirby- Bauer disc diffusion method by using 18 antibiotics for Gram positive bacteria and 19 antibiotics for Gram negative bacteria. Later, the MDR isolates were grouped by amplified ribosomal DNA restriction analysis (ARDRA) and 16S rRNA sequencing with phylogeny were performed to confirm the bacteria at species level. Results: A total of 38 bacterial isolates were obtained from the sample. Enterobacter spp. isolates showed maximum resistance against Amoxicillin, followed by Ampicillin and Aztreonam (80% each) and one isolate showed highest antibiotic resistance (15 out of 19) among all the isolates. In addition, Staphylococcus spp. and Exiguobacterium spp. isolates showed 100% resistance against Penicillin, Ampicillin, Oxacillin, Erythromycin, Lincomycin and Cefotaxime. On the contrary, all of the isolates of Escherichia spp., Bacillus spp., Proteus spp. were sensitive to all tested antibiotics. Surprisingly, 20 MDR isolates were showing resistance to at least 2 antibiotics. Subsequently, three distinct genera of these MDR isolates were identified by ARDRA; the strains Enterobacter cloacae (75%), Staphylococcus warneri (15%) and Exiguobacterium aurantiacum (10%) were confirmed by the 16S rRNA phylogenetic analysis. Conclusion: We found that cell phones can act as reservoirs of multidrug-resistant pathogens, causative agents for Hospital-acquired infections. An effective hygiene practice for health care personnel should be introduced to prevent the cross-contamination by their cell phone Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 643-656